Development of A Multicultural Based Character Education Learning Module in The “Nusantara Dance I” Course, Department of Dance Drama Music Education, Faculty of Arts and Culture, Universitas Negeri Gorontalo - Djafar, Nurlia; Rahim, Maryam; Bouti, Suleman; Zubaidi, Mohamad (International Journal of Educational Research & Social Sciences, 2026)
This study aimed to develop a Multicultural-Based Character Education Learning Module through the Tidi Lo Polopalo dance in the Nusantara Dance I course at the Department of Dance–Drama–Music Education, Faculty of Arts and Culture, Universitas Negeri Gorontalo. The study employed a Research and Development (R&D) method using Sugiyono’s stages, namely: identifying potentials and problems, data collection, product design, expert validation, design revision, limited try-out, product revision, and broader field implementation. A mixed-methods approach was applied: qualitative methods were used to explore character values and the multicultural context embedded in the Tidi Lo Polopalo dance, while quantitative methods were used to test module effectiveness through descriptive statistics and t-tests (independent and paired). The participants were students enrolled in the Nusantara Dance I course, divided into an experimental group using the module and a control group using conventional teaching materials. The results indicated that the developed module was rated highly valid by content, language, media experts, and cultural practitioners, with average scores above 85%. Practicality testing through lecturer and student questionnaires showed the module was “highly practical” (85–100%). Effectiveness analysis using a paired t-test yielded t = 10.16 > ttable = 2.093 (α = 0.05), indicating a significant improvement between pretest and posttest scores in the experimental group. Descriptively, the average learning outcome increased from 31.5 to 69.9 after module implementation. The module was proven valid, practical, and effective in enhancing students’ understanding of character values (discipline, cooperation, responsibility, religiosity, tolerance) and their multicultural awareness through the local cultural context of Gorontalo. The final product is a contextual dance learning module rooted in local wisdom as an implementation of culture-based character education.